Application of non-local physical kinetics in the theory of plasmoids. Version of Gagarin air catastrophe - B. V. Alexeev (Тонкие химические технологии)
The existence of solitary plasma objects in a bounded region is established by the methods of non-local physics. The unified generalized non-local theory is applied for mathematical modeling of quantum solitons. Ball lightings are quantum solitons – plasmoids which reach stability as a result of equalizing of corresponding quantum pressures of the non-local origin and the solitary electric forces. The delivered theory demonstrates the great possibilities of the generalized quantum hydrodynamics in the investigation of quantum solitons. The theory leads to solitons as typical formations in the generalized quantum hydrodynamics. The explanation of Gagarin catastrophe is explained as the result of the interaction of MIG 15 UTI with a plasmoid.